2022
DOI: 10.3390/vaccines10040605
|View full text |Cite
|
Sign up to set email alerts
|

Diminished Short- and Long-Term Antibody Response after SARS-CoV-2 Vaccination in Hemodialysis Patients

Abstract: Short-term studies have shown an attenuated immune response in hemodialysis patients after COVID-19-vaccination. The present study examines how antibody response is maintained after vaccination against SARS-CoV-2 in a large population of hemodialysis patients from six outpatient dialysis centers. We retrospectively assessed serum antibody levels against SARS-CoV-2 spike protein and nucleocapsid protein (electrochemiluminescence immunoassays, Roche Diagnostics) after COVID-19-vaccination in 298 hemodialysis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…for patients with kidney disease given this 3-dose combination (compared to 2-dose), clinically corroborating our evidence [37]. Similar studies on HD patients that were older than the control group, had patient groups with mean age ranging from 52-86 years [38][39][40][41][42], showing our HD cohort (mean age 54.1 years) to be comparatively young, though of similar age and gender distribution to other CKD patient groups studied in Sri Lanka [43].…”
Section: Discussionsupporting
confidence: 86%
“…for patients with kidney disease given this 3-dose combination (compared to 2-dose), clinically corroborating our evidence [37]. Similar studies on HD patients that were older than the control group, had patient groups with mean age ranging from 52-86 years [38][39][40][41][42], showing our HD cohort (mean age 54.1 years) to be comparatively young, though of similar age and gender distribution to other CKD patient groups studied in Sri Lanka [43].…”
Section: Discussionsupporting
confidence: 86%
“…Fragile patients, such as patients with haematological malignancies and haemodialysis, show an overall reduced response to anti-SARS-CoV-2 vaccination than healthy individuals 26 , 27 . Additionally, some Authors reported that fragile patients have a significantly more substantial decline of anti-SARS-CoV-2 antibody titers within 6 months compared to healthy individuals 28 , 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Previously infected patients might have developed immunity but the magnitude and the durability of this protection are variable [23] [24]. Many data suggest that patients receiving vaccination after a previous SARS-CoV-2 infection present the best antibody response [25]. This is consistent with many studies that identified duration in dialysis as a risk factor associated with a faster immunity decline as well as the type of dialysis, male sex, type of vaccine, and use of immunosuppressive drugs [23] [26] [27].…”
Section: Discussionmentioning
confidence: 99%